King of the Animals : Stories - Russell, Josh (Book collections on Project MUSE., 2021)
"In forty-three stories, Josh Russell's "King of the Animals" explores love and heartbreak, growing up and growing old, cities and suburbs, the fantastic and the everyday. A teenager and his family seek asylum in an Atlanta IKEA after their split-level is burned down because his father made fun of an autocrat's bad grammar. A man remembers how seeing a snapshot of his sister naked changed his life-and hers too. A talking doll fails her spelling test and a king made of sugar and flour watches Fox News and smokes dope with the neighbor kid. A college student ponders the philosophical implications of a poetry-fueled one-night stand and a father worries he's the reason his adult child hoards dogs. In prose lyrical and precise, Russell shows us how the extraordinary and the commonplace are entwined-and causes us to wonder why we ever thought them separate"--